Surgical management of spontaneous in-the-bag intraocular lens and capsular tension ring complex dislocation - Gunenc, Uzeyir (Medknow Publications & Media Pvt Ltd, 2014)
We describe a technique to manage late spontaneous intraocular lens (IOL) and capsular tension ring (CTR) dislocation within the intact capsular bag. The subluxated IOL and CTR complex can be positioned in a closed chamber and fixed to the pars plana at both 3 and 9 o’clock quadrants with the presented ab externo direct scleral suturation technique which provides an easy, safe and effective surgical option for such cases.